Nominal and real wage rigidity: Does nationality matter? - Sónia Cabral; Cláudia Duarte (IZA Journal of European Labor Studies, 2014)
We assess the differences in downward nominal and real wage rigidity between natives and immigrants in Portugal, using a matched employer-employee database and the International Wage Flexibility Project (IWFP) methodology. This methodology estimates a notional or counterfactual distribution that would prevail under wage flexibility and compares it to the empirical wage distribution. The estimated measures of wage rigidity capture the share of workers that received a wage freeze but would receive a wage cut in the absence of rigidity. We found that the differences between natives and immigrants are not substantial, but immigrants are more prone to institutional-related rigidities.
Keywords: F22; J31; J61; 330; Immigration; Wage rigidity; Matched employer-employee data